Marketing Strategy of Agricultural Products in Building Farmers Performance Through Digital System in Mowila Village, Mowila District, Konawe Selatan Regency - Ahsan Qasas; Eka Dharma Putra Marhanto; La Ode Keeke; Mega Liliana Hardidin; Fajar Ridha (International Journal of Management and Education in Human Development, 2022)
Problems that cause the marketing system of agricultural products to be inefficient including weak infrastructure and market information, relatively small agricultural scale, lack of knowledge from marketing actors regarding grading and handling, high transaction costs and lack of good marketing policies. Mowila Village is one of the villages in Mowila District, South Konawe Regency. Most of the people in Mowila Village are farmers. The problem faced by the community is the marketing of agricultural products. The low bargaining position of farmers causes the price received by farmers to be low so that it will affect farmers' income. To overcome the problems faced by farmers, farmers need to know the marketing system of agricultural products starting from the procurement of raw materials (inputs) to the marketing of agricultural products. In addition, online marketing (digital marketing) can be used as an alternative in conveying information on the products produced, so that limitations in conducting sales transactions for agricultural products can be overcome, and can create a sales system that is more effective and efficient.